Identification of copy number variations through whole genome resequencing between Jiuyishan and Hyplus rabbits - Wang, Yuanlang; Wang, Jinzi; Ding, Haisheng; Yang, Lianxi; Zhao, Huiling; Huang, Dongwei (Frontiers in Veterinary Science, 2025)
Copy number variations (CNVs), which include duplications and deletions of DNA segments, are significant structural variants that play crucial roles in the genetics of complex traits in livestock. High-throughput sequencing technologies enable the systematic identification of structural variants across genomes. However, CNV-based analyses of whole-genome sequencing data in rabbits remain largely unexplored. Herein, we characterized genome-wide CNVs of two rabbit breeds, Jiuyishan rabbit (JY) and Hyplus rabbit (HP), using whole-genome resequencing to elucidate their genetic characteristics and selection signatures. In total, 5,599 CNV regions (CNVRs) were identified between JY and HP, covering 0.98% of the reference genome. To identify selection signatures, we employed variance stabilizing transformation (Vst) values, selecting the top 1% of CNVRs with the highest Vst values, resulting in 56 CNVRs. These CNVRs harbored 27 genes. Functional analyses indicated that these genes were associated with important traits such as growth (HOMER1, NOS1AP, PDE4B, LEPROT) and reproduction (FRAS1, CFAP43, TM9SF2, and CTNND2). This study aims to enhance our understanding of CNVs and selection signals in rabbits, provide insights into the genetic differences between Chinese indigenous breeds and Western commercial lines, and offer valuable resources for investigating the genetic basis of complex traits.